Cultivation and Farming Analysis of Red Chili Intercropping with Celery - Syafri Edi; Suharyon Suharyon (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Intercropping is an alternative that should be developed especially to make maximum use of the land. Aromatic plants such as celery contain essential oils which, among other things, act as pest repellents. Therefore, celery plants can be used as a way of controlling pests by intercropping with chili plants as the main crop. This study aimed to determine the cultivation technology and analysis of the intercropping farming of red chilies with celery at the farmer level. The research was conducted at the Mekar Sari Farmer Group, Paal Merah Village, Paal Merah District, Jambi City, Jambi Province in October 2018. The data collected included primary data in the form of information from farmers as well as secondary data and conditions of the research area, social and economic potential. Primary data were collected using survey techniques, namely interviews with farmers and key information using a questionnaire. Samples were randomly assigned to a population of 15 farmer cooperator farmers who were intercropping red chili and celery at the study site. The data analysis technique included tabulation analysis which was used to understand the farmers' financial farming conditions, and the economic feasibility analysis uses the R/C ratio. The results of the research on the intercropping of red chili and celery, without considering the labor costs in the family, showed that this business was profitable with a total profit of 20,553,500,-IDR This farming has benefited from the production of celery as much as 405 kg, production of red chilies as much as 585 kg, and BEP prices of 15,495,-IDR/kg of celery and 14,143,-IDR/kg of red chilies. The R/C ratio value of 2.